DOP43 Long-term efficacy of tofacitinib in patients who received extended induction therapy: results of the OCTAVE open study for tofacitinib delayed responders. (25th January 2019) - Rubin, D T; Dubinsky, M C; Lukas, M; Quirk, D; Nduaka, C I; Maller, E; Lawendy, N; Kayhan, C; Fan, H; Woodworth, D A; Chan, G; Su, C
Abstract: Background: Tofacitinib is an oral, small-molecule JAK inhibitor approved in several countries for the treatment of ulcerative colitis (UC). The efficacy and safety of tofacitinib was shown in three Phase 3, randomised, placebo-controlled trials in patients with moderately to severely active UC. 1 Patients who received tofacitinib 10 mg twice daily (BID) for 8 weeks in OCTAVE Induction 1 and 2 (NCT01465763 and NCT01458951) and did not achieve clinical response—ie, induction non-responders (IndNR)—could enter an ongoing, Phase 3, multi-centre, open-label, long-term extension (OLE) study (NCT01470612). Data up to 3 years for IndNR patients who responded to extended induction with tofacitinib 10 mg BID (delayed responders) are presented. Methods: We present an update of previous analyses of delayed responders to 16 weeks of tofacitinib 10 mg BID (8 weeks' induction + 8 weeks' OLE; as of November 2017, database not locked). Patients who did not show clinical response after 16 weeks on tofacitinib 10 mg BID were required to discontinue. For delayed responders, clinical response, remission, and mucosal healing (MH) were evaluated at Months (M) 2, 12, 24, and 36 in the OLE study. Subgroup analysis by prior tumour necrosis factor inhibitor (TNFi) failure status was performed. Results: Of 295 IndNR patients, 50.7% achieved clinical response (delayed responders) by OLE M2, of whom 72.2%, 61.3%, and 54.3% showed clinical response at M12, M24, and M36, respectively. Corresponding values starting at M12 for MH were 56.8%, 52.7%, and 51.4%, respectively; approximately 45% of patients were in remission at each time point after M2 (Table 1). Analyses by prior TNFi failure subgroup showed similar trends over time. M12 efficacy measures of delayed responder patients were similar to M12 responses of 8-week tofacitinib 10 mg BID clinical responders who stayed on this dose in OCTAVE Sustain (41.0% remission; 46.2% MH; 61.8% clinical response). Proportions of delayed responder patients with adverse and safety events of special interest were similar to 8-week clinical responder patients. Conclusions: The majority of delayed responder UC patients who achieved clinical response after extended induction with tofacitinib 10 mg BID demonstrated a durable response up to 3 years. A substantial number of patients maintained clinical response, MH and remission. Effects were generally similar regardless of prior TNFi failure status. Proportions of delayed responder patients who achieved clinical response, MH and remission at M12 were similar to patients who responded to 8 weeks of treatment. Table 1. Summary of efficacy endpoints of delayed responder patients in OLE (NRI). Reference 1. Sandborn WJ et al. Tofacitinib as induction and maintenance therapy for ulcerative colitis. N Engl J Med 2017;376:1723–36.https://www.nejm.org/doi/full/10.1056/NEJMoa1606910